Temporary Protection of H-Phosphinic Acids as a Synthetic Strategy - Coudray, Laëtitia (2009)
H-Phosphinates obtained through various methodologies are protected directly via reaction with triethyl orthoacetate. The resulting products can be manipulated easily, and various synthetic reactions are presented. For example, application to the synthesis of aspartate transcarbamoylase (ATCase) or kynureninase inhibitors are illustrated. Other reactions, such as Sharpless’ asymmetric dihydroxylation, or Grubbs’ olefin cross-metathesis are also demonstrated.